2018
DOI: 10.5194/tc-2017-271
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Characteristics and fate of isolated permafrost patches in coastal Labrador, Canada

Abstract: Abstract. Bodies of peatland permafrost were examined at five sites along a 300 km transect spanning the isolated patches permafrost zone in the coastal barrens of southeastern Labrador. Mean annual air temperatures ranged from +1°C in the south (latitude 51.4°N) to -1.1°C in the north (53.7°N) while mean ground temperatures at the top of permafrost varied 10 respectively from -0.7°C to -2.3°C with shallow active layers (40-60 cm) throughout. Small surface offsets due to wind scouring of snow from the crests o… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 66 publications
0
12
0
Order By: Relevance
“…As for other types of permafrost, the relative stability of peat plateaus is also related to their slow response time to changes on the climate forcing (Throop et al, ). On the one hand, plateaus that are high enough to both (i) have low winter snow depths and (ii) drain toward the surrounding mires benefit from favorable conditions for permafrost, even in a particularly warm year as 2015–2016, with some peat plateaus being in equilibrium with the climate of the last decades (Way et al, ). On the other hand, plateaus with higher winter snow depth are likely to subside progressively due to excess ice melt (Westermann et al, ), and eventually lose their ability to drain water to the surrounding wet mire, so that permafrost is no longer stable.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…As for other types of permafrost, the relative stability of peat plateaus is also related to their slow response time to changes on the climate forcing (Throop et al, ). On the one hand, plateaus that are high enough to both (i) have low winter snow depths and (ii) drain toward the surrounding mires benefit from favorable conditions for permafrost, even in a particularly warm year as 2015–2016, with some peat plateaus being in equilibrium with the climate of the last decades (Way et al, ). On the other hand, plateaus with higher winter snow depth are likely to subside progressively due to excess ice melt (Westermann et al, ), and eventually lose their ability to drain water to the surrounding wet mire, so that permafrost is no longer stable.…”
Section: Discussionmentioning
confidence: 99%
“…Kurylyk et al () reported that, for forested peat plateaus, thaw‐induced surface evolution modifies the surface albedo, resulting in another positive feedback on permafrost degradation. In addition, modeling experiments showed that palsas and peat plateaus could persist or quickly vanished depending on the chosen climate scenario (Way et al, ), highlighting the uncertainty of future climate projections as a decisive factor when modeling the fate of these permafrost features.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of UAVs has been growing within the scientific, commercial, and government spheres as a tool to rapidly collect inexpensive 3D topographic information [22,23]. A wide range of environmental applications [23,24] extend to permafrost environments [25], where UAV optical imagery has supported vegetation classifications and disturbance assessments [26,27], visualization of moraine and arctic mine tailing dynamics [28,29], delineation of alluvial fans [30], assessment of local permafrost distribution [31], and the topography of ice-wedge polygonal networks [32]. Despite these demonstrated applications, recent advances in UAV technology have only recently been utilized to quantify permafrost dynamics and the related impacts to infrastructure.…”
Section: Introductionmentioning
confidence: 99%